A zebrafish hox gene acts before gastrulation to specify the hemangioblast. Issue 6 (17th April 2020) - Zhang, Changqing; Featherstone, Mark
Summary: Hox genes encode transcription factors that have been implicated in embryonic, adult and disease processes. The earliest developmental program known to be directed by Hox genes is the timing of ingression of presumptive axial mesoderm during gastrulation. We previously used morpholino (MO)‐based knockdown to implicate the zebrafish hoxd4a gene in the specification of the hemangioblast, an event occurring at pre‐gastrulation stages, well before the earliest known Hox gene function. The precise time at which hoxd4a function is required for this specification is not defined. We therefore fused the hoxd4a coding region to the human estrogen receptor (hER T2 ). Following co‐injection of anti‐ hoxd4a MO with mRNA encoding the Hoxd4a‐ER T2 fusion protein, hemangioblast specification was fully rescued when embryos were exposed to the estrogen analog 4‐hydroxy‐tamoxifen (4‐OHT) at 4 hr post‐fertilization (hpf), but only poorly at 6 hpf and not at all at 8 hpf, thereby defining a pre‐gastrulation role for Hoxd4a, the earliest developmental function of a vertebrate Hox gene so far described. Both DNA binding and interaction with cofactor Pbx were further shown to be required for rescue of the morphant phenotype. Confirmation of the morphant phenotype was sought via the generation of hoxd4a null mutants using CRISPR/Cas9 technology. Null mutants of hoxd4a up to the third generation (F3 ) failed to recapitulate the morphant phenotype, and were largely refractory to the effects of injected anti‐ hoxd4a MO suggesting the action of genetic compensation.